2013
DOI: 10.5267/j.msl.2013.07.016
|View full text |Cite
|
Sign up to set email alerts
|

A social work study on the effect of gender and marital status on job satisfaction

Abstract: Job satisfaction plays an essential role on having happy society since people may have better lives when they fully satisfied with their jobs. In this paper, we present an empirical study to investigate the effect of marital status as well as educational background on job satisfaction. The study performs the study among university employees of Khomeinishar branch located in province of Esfahan, Iran and all questions are designed in Likert scale of 1-5 based on Brayfield & Rothes Index of job satisfaction. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The study has detected no relationship between gender and job satisfaction and the results are consistent with Iravani et al (2013). Iravani et al (2012) performed an empirical survey to measure the effect of stress among people with different gender and reported no difference among employees with different genders.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The study has detected no relationship between gender and job satisfaction and the results are consistent with Iravani et al (2013). Iravani et al (2012) performed an empirical survey to measure the effect of stress among people with different gender and reported no difference among employees with different genders.…”
Section: Resultssupporting
confidence: 64%
“…They also reported that there were four important factors of role of ambiguity, quantitative overload, career development and handling other workers' responsibilities played important role on job satisfaction and managing career development had important effect on the performance of accountants. Iravani et al (2013), in other investigation, investigated the impact of marital status as well as educational background on job satisfaction among university employees. The survey detected that there was no difference between female and male employees in terms of job satisfaction, marital status had no significance on job satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Khodaei et al (2013) performed a study on the effect of social capital on job satisfaction and citizenship behavior among employees of a governmental university in Iran and confirmed that there were some positive and meaningful relationship between social capital and job satisfaction. Iravani et al (2013) performed a social work study on the effect of gender and marital status on job satisfaction. They reported that there was no difference between female and male employees in terms of job satisfaction and confirmed that marital status had no significance on job satisfaction.…”
Section: Introductionmentioning
confidence: 99%